First Report of Echinococcus equinus in a Donkey in Turkey - Simsek, Sami; Roinioti, Erifylli; Eroksuz, Hatice (Korean Soc Parasitology, Seoul Natl Univ Coll Medi, 2015)
A 2-year-old female donkey (Equus asinus) was euthanized in the Pathology Department of Firat University, Elazig, Turkey. Necropsy disclosed the presence of 7 hydatid cysts distributed throughout the lung parenchyma. One of those cysts represented the parasite material of the present study and was molecularly identified through sequencing of a fragment of cytochrome c oxidase subunit 1 (CO1) and nicotinamide adenine dinucleotide dehydrogenase subunit 1 (NADH1) gene, as Echinococcus equinus. The generated CO1 sequence supports the presence of the dominant haplotype as has been described in Europe and Africa. The NADH1 sequence was found similar to sequences reported in equids in Egypt and the United Kingdom. The molecular identification of E. equinus in a donkey is being reported for the first time in Turkey.
Keywords: Echinococcus equinus; donkey; molecular identification; Turkey